The Abolition of National Exams: A Slap for Education System in Indonesia - Sihombing, Lambok Hermanto; Rachman, Fanny Fanani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research article is analyses the ineffectiveness of National Exams to be conducted specifically for the measurement for graduation that actually did not become the one to be a measurement tools as there are still school final examinations that may become other measurement tools for the student graduation. As there are idea of abolishing the national exams and replace it to other measurement for graduations, the author thoughts that there should be an effort on finding better measurement for graduation. Further, it explores more reason on why the National Exams became ineffective. The author takes this case in order to search for academic perspective in viewing the National Exams ineffectiveness and should be replaced to other measurement tools for high school graduation.